Countdown in Sudan: Between compromise and war - scenarios until 2011 - Annette Weber; Wibke Hansen (Stiftung Wissenschaft und Politik (SWP), 2010)
With barely a year until the crucial vote on independence for Southern Sudan in January 2011, the peace process is in trouble. The independence referendum is sup-posed to mark the end of a six-year interim period that began in 2005 with the signing of the Comprehensive Peace Agreement (CPA) between the central government in the North and the rebel movement in the South. But patchy implementation of the peace agreement, festering mistrust between the parties and worsening political tensions in the run-up to the April 2010 elections are endangering stability in the country and reducing the chances that the referendum can pass off peacefully. If the peace process fails, the humanitarian consequences could be even graver than in Darfur. The international community must act decisively and in partnership to create the preconditions for a peaceful referendum and a minimum of stability thereafter - whether that is in one country or two
Keywords: 320